Deregulation, listing and delisting - Loveland, Robert; Mulherin, J. Harold; Okoeguale, Kevin (Journal of Corporate Finance, 2021)
We study patterns of new lists, delisting and mergers in deregulated industries in the 1973 to 2017 period. Consistent with prior research, we find that merger activity tends to cluster in deregulated industries. But we provide new evidence that new lists and overall delisting also cluster in deregulated industries, with new lists preceding delisting. We also find that deregulated industries are growing in size and value prior to deregulation and grow significantly larger, more valuable and more competitive following deregulation. The results are consistent with the linkage of deregulation and industries undergoing significant change; deregulation aids in industry adaptation to change and facilitates expansion. Moreover, the results provide a specific mechanism by which industries undergo event waves.